Tata Kelola Fintech Syariah untuk Perlindungan Konsumen Digital dalam Hukum Islam - Ananda Rauf Nurhidayah Isnaini (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2026)
This study analyzes the governance of Islamic financial technology (fintech) in protecting digital consumers based on the principles of Islamic law. The rapid development of digital financial services has encouraged the expansion of Islamic fintech in Indonesia, but it has also created various challenges related to consumer protection, data privacy, transparency of digital transactions, and accountability of digital platforms. This study employs normative legal research using a library research approach. The research applies statutory and conceptual approaches by examining regulations, Islamic legal principles, and academic literature related to Islamic fintech governance and digital consumer protection. The findings reveal that the governance of Islamic fintech in Indonesia has not been fully integrated in ensuring comprehensive digital consumer protection. Weak supervision, misuse of personal data, unclear digital contracts, and limited integration between financial regulations and sharia compliance remain significant challenges in Islamic fintech services. In the perspective of Islamic law, the principles of maqashid sharia, amanah, transparency, justice, and hifz al-mal provide an important normative foundation for strengthening digital consumer protection. This study also demonstrates that Islamic digital governance is required to integrate consumer protection, privacy governance, accountability, transparency, and sharia compliance within digital financial services. The study contributes conceptually to the development of Islamic digital governance as an integrative framework for strengthening ethical, transparent, and consumer-oriented Islamic fintech governance in the digital economy era.